2023
DOI: 10.3390/buildings13071706
|View full text |Cite
|
Sign up to set email alerts
|

Circularity Indicators as a Design Tool for Design and Construction Strategies in Architecture

Abstract: This study addresses the challenges and barriers associated with the implementation of circular economy principles in architectural design and construction practices. It highlights the fragmented knowledge and lack of a unified approach to circular design as a major obstacle hindering the adoption of circularity. The existing frameworks for assessing circularity, such as the Material Circularity Indicator (MCI) protocol and the Level(s) assessment protocol, are applied to two projects with a high degree of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Steinmann et al (2019) proposed a material quality indicator based on the energy use of recycled products to assess circularity in the economy [28]. Other researchers have explored tools, such as material flow models and circularity scoring methods [29], for assessing circularity and material selection in the built environment, as well as setting up circularity strategies as early as the design stage [30]. However, a major research gap is in defining and implementing CE indicators that can also account for the presence and the impact of hazardous materials, which can undermine the recyclability capacity of construction materials.…”
Section: Circular Indicators Of Building Materialsmentioning
confidence: 99%
“…Steinmann et al (2019) proposed a material quality indicator based on the energy use of recycled products to assess circularity in the economy [28]. Other researchers have explored tools, such as material flow models and circularity scoring methods [29], for assessing circularity and material selection in the built environment, as well as setting up circularity strategies as early as the design stage [30]. However, a major research gap is in defining and implementing CE indicators that can also account for the presence and the impact of hazardous materials, which can undermine the recyclability capacity of construction materials.…”
Section: Circular Indicators Of Building Materialsmentioning
confidence: 99%
“…This naturally results in a majority of Review publications, aligning with previous patterns, giving an even distribution between DfD and Reuse. The topics emphasized are LCA [21,57,[69][70][71], adaptability [21][22][23][24]57,69,70,72,73], and the potential of CE integration within specific materials like concrete [18,22,24,74], timber [23,75], and steel [73,[76][77][78][79][80], which is further explored in Section 4.5. Additionally, through the further examination of publications within the CE investigation, the recurrent critical research gaps have been identified as the need for precise standardization [21][22][23]57,74,77,78,81], digital tool integration [81], and overcoming challenges in policy [69,76,78], market acceptance [73,78], and industry-wide adoption to advance CE [18,22,72,74,…”
Section: Research Type and Circular Designmentioning
confidence: 99%
“…CT: [103], SC: [15,86,[104][105][106] CT: [29,33] CE: [21][22][23][24]69,72,77,81,82], SC: [19] SC: [17,25,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Case Studies Design Development Framework Review Technical Paper CT = Computational Tool, CD = Computational Design, SC = Structural Concept, CE = Circular Economy Investigation.…”
Section: Deconstructionmentioning
confidence: 99%